SOSIALISASI DAMPAK CANDU GADGET TERHADAP KESEHATAN FISIK DAN PSIKIS SERTA DEMONSTRASI SENAM MATA DI SMA MUHAMMADIYAH 1 PURWOKERTO - Jumiati Riskiyani Dwi Nandia; Meida Laely Ramdani (Universitas Pahlawan Tuanku Tambusai, 2022)
The COVID-19 pandemic has paralyzed several sectors of life, one of which is the education sector. In the midst of this situation, the government's effort to keep the education program running is by implementing distance learning via online. In this case, students must adapt to the use of gadgets as online media in carrying out their daily learning activities. The purpose of this service is to provide understanding and knowledge of the impact of using gadgets on physical and psychological health for students at SMA Muhammadiyah 1 Purwokerto. The method used in this community service is to provide direct socialization to 60 students of SMA Muhammadiyah 1 Purwokerto regarding the positive and negative impacts of using gadgets on physical and psychological health and demonstrations of eye exercises to reduce eye fatigue due to exposure to gadgets. Results: In this activity, the results obtained from the knowledge of students before being given socialization with good categories (15%), sufficient (40%), and less (45%) and after being given socialization, students' knowledge was good (60%), quite (35%), and less (5%). From this community service activity, it is hoped that students will better understand the positive and negative impacts on health from excessive use of gadgets and direct students to get used to managing time so that activities are more productive without gadget addiction. Keywords: Socialization, Demonstration of eye exercise, Gadget addiction